The Central Nervous System and Psychosocial Factors in Primary Microvascular Angina - Cattaneo, Mattia; Halasz, Geza; Cattaneo, Magdalena Maria; Younes, Adel; Gallino, Camilla; Sudano, Isabella; Gallino, Augusto (Frontiers in Cardiovascular Medicine, 2022)
Patients diagnosed with ischemia without obstructive coronary artery disease (INOCA) comprise the group of patients with primary microvascular angina (MVA). The pathophysiology underlying ischemia and angina is multifaceted. Differences in vascular tone, collateralization, environmental and psychosocial factors, pain thresholds, and cardiac innervation seem to contribute to clinical manifestations. There is evidence suggesting potential interactions between the clinical manifestations of MVA and non-cardiac conditions such as abnormal function of the central autonomic network (CAN) in the central nervous system (CNS), pain modulation pathways, and psychological, psychiatric, and social conditions. A few unconventional non-pharmacological and pharmacological techniques targeting these psychosocial conditions and modulating the CNS pathways have been proposed to improve symptoms and quality of life. Most of these unconventional approaches have shown encouraging results. However, these results are overall characterized by low levels of evidence both in observational studies and interventional trials. Awareness of the importance of microvascular dysfunction and MVA is gradually growing in the scientific community. Nonetheless, therapeutic success remains frustratingly low in clinical practice so far. This should promote basic and clinical research in this relevant cardiovascular field investigating, both pharmacological and non-pharmacological interventions. Standardization of definitions, clear pathophysiological-directed inclusion criteria, crossover design, adequate sample size, and mid-term follow-up through multicenter randomized trials are mandatory for future study in this field.